Effect of BAP and NAA on Callus Emergence Time of Dumbaya Young Leaf Explants in Vitro - Walangadi, Farhana Rahmatia; Ahmad, Jusna; Pagalla, Devi Bunga; Kandowangko, Novri Youla; Febriyanti, Febriyanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Momordica cochinchinensis, locally known as Dumbaya in Gorontalo Province, is a traditional medicinal plant with underutilized potential due to the extremely hard morphology of its seed coat. This physical barrier limits the penetration of water, air, and nutrients, thereby reducing the success rate of seed germination and plant propagation. The challenge of propagating plants that are difficult to reproduce sexually, such as dumbaya, can be addressed through various approaches, one of which is asexual reproduction using tissue culture techniques. This study aims to address propagation constraints by applying tissue culture techniques supplemented with Plant Growth Regulators (PGRs), specifically BAP (Benzyl Amino Purine) and NAA (Naphthalene Acetic Acid), which are critical factors in successful in vitro plant regeneration. The combination of Benzyl Amino Purine (BAP) and Naphthalene Acetic Acid (NAA) is a commonly used Plant Growth Regulator (PGR) for inducing callus formation and organogenesis, where BAP is effective in stimulating shoot formation, while NAA plays a role in root induction. The research employed an experimental method using a Completely Randomized Design (CRD) with five treatment levels: H0: MS + 0 ppm NAA + 0 ppm BAP; H1: MS + 1.5 ppm NAA + 0.5 ppm BAP; H2: MS + 3.0 ppm NAA + 0.5 ppm BAP; H3: MS + 1.5 ppm NAA + 1.0 ppm BAP; and H4: MS + 3.0 ppm NAA + 1.0 ppm BAP. Each treatment was replicated three times. The results showed that treatment H1 produced the earliest callus formation, with an average callus initiation time of 7 days after planting.